Building routing overlays in disrupted networks: inferring contacts in challenged sensor internetworks. (14th November 2012) - III, Edward J. Birrane
Current routing approaches in Delay–Tolerant Networks (DTNs) focus on the exchange of information across homogenous addressing domains without addressing DTNs constructed from a set of cooperating networks using different protocols and mobility models. We present inference–based Contact Graph Routing (iCGR), a logical–level routing method for DTN internetworks that comprise heterogeneous data link and/or network layers. iCGR constructs a time–variant 'Contact Graph' at each node in the network to describe logical contact opportunities regardless of underlying physical media access. The iCGR approach extends the established approach of graph based routing beyond static networks and provides a mechanism for multiple data link protocols to co–exist in an internetwork. This overlay–routing approach allows otherwise routing–protocol–incompatible networks to join an internetwork with little overhead. iCGR is validated through NS3 simulation of a DTN internetwork comprising manually asserted contact opportunities, a non–DTN routing protocol, and probabilistic DTN routing protocol.